A construção do sentido nas capas de revista Veja de 2016 e 2017 com assunto política no âmbito nacional - FERRANTI, Rúbna Laíse Pereira dos Santos (2019)
This work has as theme the construction of meaning of covers from “Veja” Magazines from years of 2016 and 2017, about politics in national environment. This work has as aim to analyze how the meanings of the covers of the exemplars are constructed; understanding what is said or implicit. It looks, also, to analyze external influences, for example, the knowledge of world that the speeches from headlines suffer. And still, it looks for observe the effects that covers can cause to society, and if the covers speeches suffer influence and how the social actors present on them are represented. From the methodological point of view were necessary, first, a bibliographic research about works of Critical Analysis of speech (ADC) and a collection of covers of magazines, for what could be made the choice of which of them would be useful for the research. In addition, it was applied a questionnaire as tool of data collection with questions related to the aim of this research. It is important to say that this is a research with qualitative and descriptive character. The results could show how a reader understands the cover of a magazine, if he or she can see which meaning effects are generated from the composition of covers and representation of social actors on them